Síntese, análise estrutural, luminescência e atividade biológica de complexos de metais de transição com ligantes derivados de benzoilidrazina e feniltiossemicarbazida - Bessega, Tiago (2019)
This work reports the synthesis and characterization of new complexes with 2,6-diacetylpyridine-bis(benzoylidrazone) (L1) and 2,6-diformylpyridine-bis(4-phenylthiosemicarbazone) (L2) ligands. The complexes [(L1)2Ce]Cl3.14H2O (L1Ce), [(L1)2Ln]Cl3.3EtOH.2H2O (L1Ln, where Ln = Sm, Eu, Gd, Tb, Dy, Ho and Er), [L2Zn(MeOH)2](NO3)2 (L2Zn), [L2Pd].MeOH (L2Pd) and [L2Pt].MeOH (L2Pt) was structurally characterized by X-ray diffraction. Lanthanide complexes had their luminescent properties investigated, while Pd, Pt and Zn complexes were studied against DNA and BSA protein interactions. Lanthanide complexes are isostructural. In all the complexes, the atom of Ln is coordinated by two ligatures L1 in a pentadentate mode, being decacoordenated, in a distorted square bipyramidal geometry. In the L2Zn complex, the metal is heptacoordinated, with bipyramidal-pentagonal geometry, with the donor set N3S2 of the ligand at the pentagonal 10 base and two molecules of methanol occupying the axial positions. In the L2Pd and L2Pt complexes, the ligand acts as a dianionic tetradentate donor, coordinating the metal in a planar square geometry. The ability of L2 ligand and its complexes to interact with DNA and bovine serum albumin (BSA) was evaluated. The interactions of the compounds L2, L2Zn, L2Pd and L2Pt with DNA were recorded by UV-vis absorption spectroscopy and the interactions between bovine serum albumin (BSA) and the compounds were quantified by steady-state fluorescence emission measurements. The L2Pd and L2Pt complexes showed strong binding constants to CT-DNA, following the increasing order of Kb values: L2Zn <L2 <L2Pd ≈ L2Pt. Molecular docking calculations were performed in order to elucidate the interaction modes between these compounds and the DNA and BSA structure. The most likely binding sites of each compound with DNA and BSA were estimated, also identifying the amino acid residues involved in the interaction.